Kajian Teknis Umur Pakai Mata Bor Menggunakan Metode Galle and Woods pada Batuan Sedimen - Aullia Bintang Jaladri; Bagus Wiyono; Wirawan Nurcahyo Utomo (Mataram University, 2026)
The operational efficiency of coal drilling at Pit Bendili, PT Kaltim Prima Coal, is directly influenced by drill bit life. This study aims to evaluate technical drilling parameters to achieve a target bit lifespan of 10.800 m using the Galle and Woods theoretical method. Evaluated parameters include Weight on Bit (WOB) and Rotational Speed (RPM) from a Sandvik D55SP drill rig (unit D162) operating in soft to very soft formations with Uniaxial Compressive Strength (UCS) values ranging from 14,14 MPa to 17,73 MPa. The Galle and Woods method mathematically models tooth and bearing wear rates to predict optimum bit replacement intervals. Results indicate that mitigating bit balling while achieving the cumulative 10.800 m target requires maintaining the pipe rotation speed constant at its maximum limit of 187 RPM and optimizing WOB within safe Sandvik operational thresholds. This parameter combination maximizes the penetration rate while minimizing premature component failure.